2001
DOI: 10.1542/peds.107.4.e46
|View full text |Cite
|
Sign up to set email alerts
|

Severe Nutritional Deficiencies in Toddlers Resulting From Health Food Milk Alternatives

Abstract: It is widely appreciated that health food beverages are not appropriate for infants. Because of continued growth, children beyond infancy remain susceptible to nutritional disorders. We report on 2 cases of severe nutritional deficiency caused by consumption of health food beverages. In both cases, the parents were well-educated, appeared conscientious, and their children received regular medical care. Diagnoses were delayed by a low index of suspicion. In addition, nutritional deficiencies are uncommon in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(127 citation statements)
references
References 24 publications
(33 reference statements)
5
116
0
6
Order By: Relevance
“…The main reasons for this change are preference for plant foods, aversion to the use of cow's milk, and prevention or treatment of cow's milk allergy, as part of strict vegetarian diets or as a consequence of the advice of professionals from alternative medicines (5). Primary use in the early years of life of mainly soy, rice, almond or oat PBBs results in nutritional risks (rickets, failure to thrive, kwashiorkor or metabolic alkalosis, among others) (6). In addition, in our country we reported a case of scurvy with bone fractures in an infant fed almost exclusively with almond beverages (7).…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…The main reasons for this change are preference for plant foods, aversion to the use of cow's milk, and prevention or treatment of cow's milk allergy, as part of strict vegetarian diets or as a consequence of the advice of professionals from alternative medicines (5). Primary use in the early years of life of mainly soy, rice, almond or oat PBBs results in nutritional risks (rickets, failure to thrive, kwashiorkor or metabolic alkalosis, among others) (6). In addition, in our country we reported a case of scurvy with bone fractures in an infant fed almost exclusively with almond beverages (7).…”
Section: Introductionmentioning
confidence: 68%
“…The nutritional disorder most often associated with consumption of soy beverages in small children is rickets and failure to thrive, along with ferropenic anemia in some cases (6,16,17) (Table II). In the published cases, soy beverages were mostly given for suspected allergy to cow's milk proteins or due to the parents' belief that it was more suitable for their child.…”
Section: Consumption Of Pbbs and Nutritional Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…A diet defi cient in calcium 16 , such as one dependent on nonforti fi ed milk substi tutes, can lead to rickets 17,18 . Nutriti onal rickets presents in the fi rst two years of life with short stature, gait abnormality, developmental delay, and characteristi c fi ndings (Table 1 8,9-15 and Table 2 9, 14,19 ).…”
Section: Types Of Ricketsmentioning
confidence: 99%
“…Venter and R. Meyer intakes of Ca, vitamin D and vitamin E are also lower than the recommended daily intakes (77) . These studies have identified maternal fears (50) , no dietetic referral (84,87) , alternative allergy testing (50) , use of an inappropriate alternative formula (85) or palatability of the chosen formula (50) as important indicators of a poor nutritional status. This evidence reinforces the need for all food-avoidance diets to be supervised by an appropriate specialist healthcare professional with nutritional knowledge such as a registered dietitian (84,88) .…”
mentioning
confidence: 99%